Gender differences in adolescent self-efficacy in sport - Manktelow, Scott Ralph (My University, 1996)
The purpose o f this study was to examine the effect of gender on sport self-efficacy in adolescents. The effect of age and sport participation on sport self-efficacy were also examined. Self-efficacy was assessed with two measures; self-efficacy to succeed in sport, and self-efficacy to initiate participation in sports. The sample was enlisted from three Thunder Bay, Ontario, high schools (n = 292) from two age groups: grade 9 and grade 12. Sport participation levels were assessed with a self-report measure of average weekly participation in sports. Self-efficacy to succeed was measured with a 9-point Likert scale using a modified Trait Sport-Confidence Inventory (Vealey, 1986), and a self-efficacy to initiate participation in sport tool. Written responses to several questions were also requested from sport nonparticipants for qualitative analysis. Quantitative results were analyzed using MANOVA. Findings identified a gender effect on self-efficacy to succeed in sport with males (x = 7.17) demonstrating higher levels than females (x = 6.75). Participation level had a main effect on both measures of self-efficacy. Age group was found to have no effect on any variables. The role of sport participation in the development of self-efficacy is discussed, including the influence of gender. Results are described in terms of self-efficacy theory as conceptualized by Bandura (1977).
Keywords: Self-efficacy; Adolescent psychology; Sports Psychological aspects